Pike-Perch (Sander lucioperca) and Rainbow Trout (Oncorhynchus mykiss) Fed with an Alternative Microorganism Mix for Reducing Fish Meal and Oil—Fishes’ Growth Performances and Quality Traits - Michaela Schafberg; Karin Loest; Andreas Müller-Belecke; Sascha Rohn (Foods, 2021)
In the last decades, several plant-based materials were used for the substitution of fish meal and oil in aquaculture. The present study evaluated the fish quality and the sensory differences of rainbow trout (Oncorhynchus mykiss) and pike-perch (Sander lucioperca) from three different feeding groups, which were fed a commercially available industrial (standard) diet, a control diet, and a special microorganism-based feed mix. This feed mainly consisted of a mix made of Rhodotorula glutinis, Crypthecodinium cohnii, and Arthrospira sp. and had 50% less fish meal and fish oil compared to typical control diets. At the beginning, the pike-perch population was six months old, and the rainbow trout population was 15 months old. The feeding study duration was 16 weeks and every four weeks the growth performance and several morphometric parameters were recorded. Afterwards, sensory evaluation took place to identify possible trends. Sensory evaluation revealed that the rainbow trout groups did not show any significant differences to the standard and control fish fillets with regard to odor, texture, and taste. The effects on rainbow trout growth performances and carcass parameters were similar to the standard group. The feed mix was not optimal for pike-perch farming, which was also reflected by significantly adversely affected growth performance and carcass parameters. The sensorial evaluation showed an opposite trend: here, only small differences in the fillets from the feed mix and standard/control diet were observed.